Developing a literature-based systems map of determinants of dietary intake in low-income groups. (30th September 2020) - Sawyer, A; van Lenthe, F; Kamphuis, C; Poelman, M; Djojosoeparto, S; Roos, G; Terragni, L; Nicolaou, M; Waterlander, W; Stronks, K
Abstract: Background: Inequalities in obesity and related non-communicable diseases pertain in part to less healthy dietary intake in disadvantaged groups. Examining determinants of intake as a complex adaptive system - i.e. interconnected determinants exerting non-linear influence on outcomes - honours the complexity of dietary choices, behaviours and intake, and could inform policies. This study used literature to map the complex system underlying dietary intake in low-income groups, to identify system structure and goals perpetuating poorer dietary outcomes. Methods: A systematic umbrella literature review examined determinants of dietary outcomes in children, adolescents and adults. Inclusion criteria were: Low-income sample; analysis by income (Non-)systematic review of quantitative/qualitative, observational/intervention studies Higher/upper-middle-income countries Exposures: individual, sociocultural, physical, political determinants/correlates; effect modifiers Excluded outcomes were: breastfeeding, alcohol and neophobia. Using causal loop diagramming, extracted data on determinants, associations and interpretation were embedded in a systems map of mechanisms driving dietary intake. System structure (e.g. sub-systems) and goals (e.g. feedback loops) were analysed. Results: A systems map of hypothesised mechanisms driving dietary intake in low-income groups was developed from 43 reviews and expert consensus. The system comprised sub-systems: 1) accessibility, 2) household resources, 3) financial constraints, 4) health/biology, 5) knowledge, attitudes and beliefs, 6) sociocultural influences. Identified sub-system goals could undermine healthy intake opportunities, e.g. energy-dense food choices for cost-efficiency, heightened exposure to energy-dense foods determining preferences. Conclusions: The literature-based systems map articulates the systemic basis of poorer dietary outcomes in low-income groups. Understanding system structure and goals will inform equitable policy. Key messages: Dietary intake in low-income groups is driven by a complex system of mechanisms which may perpetuate poorer dietary outcomes. Existing literature was synthesised as a systems map; identification of structures and goals of the system can inform health equity policies.